Information support for institutionalization of CIS trans-border cooperation - Тихомирова, Євгенія Борисівна; Tykhomyrova, Yevheniia B. (Turiba University, 2013)
The importance of the trans-border cooperation institution formation, which shows the problem of the institutionalization building in the field of the trans-border cooperation and the determination of the results of the made institutionalization decisions are analyzed. The author claims that the institutional basis of the trans-border cooperation of the CIS countries consists of formal norms and rules, which are shown in the legal and normative acts, which act on the different levels of the Commonwealth countries interaction. The organizational forms, in particular of the trans-border cooperation information support on the level of the intergovernmental institutions and structural subdivisions of the CIS community, structural, central, regional and local (municipal) authorities, who refer to the trans-border cooperation, a specific organizational form of the trans-border cooperation, borrowed from the EU experience, which can be defined as European region, are investigated. The author concludes that the institutionalization component of the CIS trans-border cooperation information support, on the one hand follows the EU experience, and on the other takes into the consideration the traditions developed on the post-Soviet space.
Keywords: institutionalization; institute; institution; information support; cluster; norms; organization; the CIS; Ukraine